2011
DOI: 10.1111/j.1467-9922.2011.00640.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Research Methods, Study Quality, and Outcomes: The Case of Interaction Research

Abstract: This article constitutes the first empirical assessment of methodological quality in second language acquisition (SLA). We surveyed a corpus of 174 studies (N = 7,951) within the tradition of research on second-language interaction, one of the longest and most influential traditions of inquiry in SLA. Each report was coded for methodological features, statistical analyses, and reporting practices associated with research quality, and the resulting data were examined both cumulatively and over time. The finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
268
3
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(284 citation statements)
references
References 102 publications
(134 reference statements)
12
268
3
1
Order By: Relevance
“…Methods for the Systematic Review Searching We focused our search on academic, peer-reviewed journals because we wanted to examine the extent of self-labeled replication in this medium, which has been identified as the primary channel for disseminating L2 research (Smith & Lafford, 2009;VanPatten & Williams, 2002). We therefore excluded replications in books, dissertations, conference proceedings, and the like, following procedures used in previous syntheses in the field (e.g., Plonsky & Gass, 2011;Plonsky, 2013). Admittedly, this left our sample susceptible to the effects of potential publication bias among journals.…”
Section: A Systematic Review Of Self-labeled Replication Aimsmentioning
confidence: 99%
“…Methods for the Systematic Review Searching We focused our search on academic, peer-reviewed journals because we wanted to examine the extent of self-labeled replication in this medium, which has been identified as the primary channel for disseminating L2 research (Smith & Lafford, 2009;VanPatten & Williams, 2002). We therefore excluded replications in books, dissertations, conference proceedings, and the like, following procedures used in previous syntheses in the field (e.g., Plonsky & Gass, 2011;Plonsky, 2013). Admittedly, this left our sample susceptible to the effects of potential publication bias among journals.…”
Section: A Systematic Review Of Self-labeled Replication Aimsmentioning
confidence: 99%
“…Bearing this in mind, the following suggestions for English SBI research are offered, many of which encompass previous suggestions for more general reform of EFL research efforts (see, e.g., Ellis;Norris & Ortega, 2000Plonsky & Gass, 2011): First of all, the value of English SBI depends on whether its effects last over time or not; few study samples in this meta-analysis included delayed posttests; thus, the need for more measurements of the persisting summary effects of English SBI is felt.…”
Section: Resultsmentioning
confidence: 99%
“…However, findings of recent surveys of the SLA research literature (e.g. Plonsky & Gass, 2011;Plonsky, 2013;Lindstromberg, 2016) do not suggest that the community of SLA researchers has the resources to conduct enough large-scale RCTs to address a good-sized proportion, let alone all, of the many worthwhile hypotheses that have been, and are being, generated. Finally, we have looked at the sampling variation of p values derived from the IS t-test.…”
Section: What An Initial P Value Foretells About a Replication P Valuementioning
confidence: 99%
“…the reliability of measurements, experimental design, and the method of statistical analysis). Focusing on observational and quasi-experimental studies relating to Long's (1983) interaction hypothesis, Plonsky and Gass (2011) surveyed 174 articles in 14 applied linguistics journals (plus two edited volumes) from the period 1980 to 2010, finding that the mean number of learners per learning condition was 22. In a survey embracing 606 quantitative studies published in two top applied linguistics journals, Plonsky (2013) found that the median number of learners per learning condition was 19.…”
Section: Introductionmentioning
confidence: 99%